A Study on the Effectiveness of the Teaching Practice Component in the Diploma in Early Childhood and Primary Education Programme - Munasinghe, D.M.W. (University of Jaffna, 2012)
Distance education as a vehicle for the delivery of course content, as well as complete academic programmes, continues to grow rapidly in the world. Distance education or distance learning is a field of education that focuses on the pedagogy, technology and instructional system design that aim to deliver education to students who are not physically “on site” as in a traditional classroom or campus. There are theoretical and practical courses given through the distance mode. Teaching practice is the most important aspect and any individual should have the competence to teach, because teaching directly affects the child who studies in the classroom. Successful teachers are not simple charismatic, persuasive and expert presenters; they should also have the knowledge, skills and techniques of making productive use of teaching materials to suit the varying levels of the learners. Therefore, teachers should have adequate teaching practice skills to teach in the classroom. Diploma in Early Childhood and Primary Education (Dip. in ECPE) programme is one of the programmes conducted by the Open University of Sri Lanka. Teaching practice is one main component that completes the programme. This research inquires whether the teaching practice component of the Dip. in ECPE programme provides adequate training to students to teach preschool and primary schools children of different ability levels, simultaneously